2011
DOI: 10.1258/acb.2011.010267
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of insulin-like growth factor-I, insulin-like growth factor binding protein-3 and cardiovascular risk factors in adolescents

Abstract: Background: The risk association between the insulin like growth factor-I (IGF-I) system and cardiovascular risk is inconclusive in adults and under-explored in adolescents. We aimed to investigate the associations between serum concentrations of IGF-I and IGF binding protein-3 (IGFBP-3) and cardiovascular risk factors in adolescents.Methods: This was a cross-sectional, population-based, observational study in a school setting with 2102 Hong Kong Chinese adolescents aged 12-19 years. Serum IGF-I and IGFBP-3 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…In obese children there are strong inverse relationships between IGFBP-1 concentrations and insulin resistance, as well as the metabolic syndrome [49]. In a Hong Kong study higher IGF-I and IGFBP-3 concentrations were observed in obesity and in relation to cardiovascular risk markers in adolescence [50]. In contrast another study has shown decreased total IGFBP-3 in obese adolescents and increased circulating IGFBP-3 protease activity and IGFBP-3 fragments [51].…”
Section: Obesitymentioning
confidence: 99%
“…In obese children there are strong inverse relationships between IGFBP-1 concentrations and insulin resistance, as well as the metabolic syndrome [49]. In a Hong Kong study higher IGF-I and IGFBP-3 concentrations were observed in obesity and in relation to cardiovascular risk markers in adolescence [50]. In contrast another study has shown decreased total IGFBP-3 in obese adolescents and increased circulating IGFBP-3 protease activity and IGFBP-3 fragments [51].…”
Section: Obesitymentioning
confidence: 99%
“…Authors of research studies have also measured liver function tests and thyroid function tests in an effort to exclude confounding factors [178]. Biochemical tests appear unlikely to replace nutritional screening tools in the foreseeable future.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Another potential explanation for the improvement is that IGF-I treatment increases respiratory muscle strength as has been shown in a previous rhGH administration study in abstinent anabolic steroid users, in which both maximal oxygen uptake and mean inspiratory pressure were increased after rhGH treatment (4). It has also been shown previously that serum IGF-I concentrations are positively correlated with hemoglobin concentrations (15). An increase in hemoglobin might explain improved aerobic performance after IGF-I treatment through enhanced oxygen delivery to exercising skeletal muscle.…”
Section: Discussionmentioning
confidence: 57%